Establishment of a pseudovirus neutralization assay for TGEV - Wang, Haojie; Chen, Jianxing; Xue, Lihong; Sun, Yue; An, Tongqing; Wang, Yue; Chen, Hongyan; Yu, Changqing; Xia, Changyou; Zhang, He (Frontiers in Immunology, 2025)
IntroductionTransmissible Gastroenteritis Virus (TGEV) is a major pathogen causing swine enteric diseases, necessitating effective control strategies. Vaccination plays a key role, but assessing vaccine efficacy remains challenging due to variations in immune response and existing detection limitations. Current antibody detection methods, such as neutralization assays and ELISA, are often subjective, labor-intensive, and time-consuming, highlighting the need for a more efficient evaluation approach.Methods and resultsThe TGEV S gene was amplified and inserted into the eukaryotic vector PM2.G-ΔG-HA to construct the recombinant plasmid PM2.G-ΔG-TGEV-S-HA. Transfecting ST cells with this plasmid, followed by infection with G*VSV-GFP/LUC, successfully produced TGEV P0 pseudoviruses. Western blot and electron microscopy confirmed the presence of TGEV S and VSV N proteins and the distinct pseudovirus morphology. Optimization determined that 0.5 μg/well of plasmid, 24 h transfection, and 24 h post-infection harvest yielded a viral titer of 106-107 TCID50/mL. The pseudoviruses exhibited strong ST cell tropism and were effectively neutralized by TGEV-positive sera. A pseudovirus-based neutralization test (pNT) was established, showing 100% sensitivity, 96.6% specificity, no cross-reactivity with PEDV, PPV, PDCoV, or PRoV, and a 94% concordance with the live virus neutralization test. The method effectively tracked antibody level changes post-TGEV vaccination.DiscussionThis study successfully developed a novel pseudovirus-based detection method, overcoming traditional assay limitations. The pNT method provides a scalable, efficient, and reliable tool for TGEV antibody evaluation, with broad potential applications in pathogen detection and vaccine assessment.